Komparasi Problematika Implementasi Kurikulum 2013 dan Kurikulum Merdeka di SMPN Tasikmalaya - Sari, Dita Kumala (Journal of Islamic Education, 2023)
This research is entitled "Comparison of Problems in the Implementation of the 2013 Curriculum and the Independent Curriculum at SMPN Tasikmalaya". The aim of this research is to determine (1) the problems of implementing the 2013 curriculum and the independent curriculum at SMPN Tasikmalaya. The type of research used in this research is descriptive qualitative. This research was carried out at 10 SMPN Tasikmalaya. The instruments used in this research were interviews, documentation and observation instruments. The data analysis technique in this research uses data validity testing techniques through triangulation. The results of research regarding the problems of implementing the 2013 curriculum include teachers still teaching using conventional methods, a lack of IT-based learning facilities, teachers still not being proficient in using IT, a lack of learning resources for students, and very many administrative systems. Meanwhile, problems with implementing the independent curriculum include difficulties in preparing learning plans, difficulties in creating learning modules, differentiated learning systems, difficulties in determining learning methods, lack of learning facilities, and difficulties in preparing assessments.